The effect of curcuminoid turmeric rhizome extract on interleukin 1ß concentration in osteoarthritis patient - Woro Rukmi Pratiwi; Nyoman Kertia (Faculty of Medicine, Universitas Islam Indonesia, 2019)
Background: Cytokine Interleukin (IL) 1ß is increased in synovial fluid and cartilage of patients with osteoarthritis (OA). Curcuminoid blocks lipopolysaccharides causing the suppression of IL 1ß production. The capability of curcuminoid to decrease IL 1ß secretion by the synovial fluid monocytes has not been previously studied. Objective: This study aimed to explore the activity of curcuminoid of turmeric rhizome extract (C. domestica Val.) in blocking the IL 1ß secretion by the knee synovial fluid monocytes of patients with osteoarthritis.Methods: This research was a prospective randomized open and blinded endpoint (PROBE) study. The subjects of the study were osteoarthritis patients who were divided into 2 groups. Subjects were administered 30 mg of turmeric rhizome curcuminoid extract (treatment group) and 25 mg diclofenac sodium capsules (control group) twice a day for 4 weeks. Knee synovial fluid was taken before and after treatment. The capability examination of IL 1ß secretion by synovial fluid monocytes was conducted by culturizing the monocyte cells. Level of IL 1ß was measured by ELISA Results: There were 80 subjects eligible to participate in the study according to the inclusion/exclusion criteria. The decrease of means of IL 1ß concentration of the curcuminoid group after the 4-week therapy was 70.24±81.46 pg/ml, while the decrease of means of diclofenac sodium was 61.90±60.42 pg/ml, with no significant difference between groups (p=0.691;95%CI:0.681-0.699).Conclusion: Curcuminoid of turmeric rhizome (C. domestica Val.) extract has the capability which is not weaker than that with diclofenac sodium in decreasing the IL 1ß secretion by synovial fluid monocytes of the OA patients’ joints.